(untitled) (Global Journal of Management and Business Research, 2015)
Management information system (MIS) is used to solve management problems in the practical life, the designing and building of the management information systems is done by using one of the systems development methodologies, Classical approach is one of these methodologies which still suffer from some critical problems when it is used in designing and building the management information systems, it consumes more time and cost during its life cycle. This paper develops a new integrated model to minimize the classical approach life cycle in designing and building the management information systems to avoid the additional consume in time and cost.